Synod on synodality: A tour of the final document - Fisher, Anthony (The Australasian Catholic record, 2025)
Synodality for communion, participation and mission for a Synodal Church: Communion, Participation, Mission: Final Document (2024) is the final text of the XVIth General Assembly of the Synod of Bishops (the "Synod on Synodality"). It was approved by the synod members and by the Holy Father and commended by him for implementation as if it were part of the ordinary papal magisterium, even if it is "not strictly normative" and still requires "several forms of mediation".